Electrolyte based on linear sulfone solvent, application of electrolyte and lithium ion battery
A linear sulfone solvent-based electrolyte with a hydrofluoroether co-solvent and additive forms stable interface films, addressing oxidation stability and temperature limitations, enhancing lithium-ion battery performance.
Patent Information
- Application Number
- CN202411359343.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-27
- Publication Date
- 2024-12-13
AI Technical Summary
Traditional carbonate-based electrolytes exhibit poor oxidation stability at higher voltages, leading to interfacial side reactions and reduced cycle life, and their high melting point and solvation energy limit lithium-ion battery performance in extreme temperatures and high-current applications.
An electrolyte composed of a linear sulfone solvent, a lithium salt, a hydrofluoroether co-solvent, and an additive, which forms quasi-hydrogen bonds to reduce lithium ion solvation energy and enhance desolvation, forming a stable interface film on graphite electrodes, enabling high-voltage operation and improved cycle stability.
The electrolyte achieves stable cycling of 4.5V lithium-ion batteries over a wide temperature range (-20 to 60°C) with enhanced rate and low-temperature performance, maintaining high energy density and cycle stability.
Smart Images

Figure HDA0005064520470000011 
Figure HDA0005064520470000012 
Figure HDA0005064520470000021
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of lithium ion battery electrolytes, and in particular relates to an electrolyte based on a linear sulfone solvent, an application thereof and a lithium ion battery. Background Art
[0002] With the development of modern society and the upgrading of energy storage demand, consumer electronics and electric vehicles urgently need lithium-ion batteries with high energy density and stable cycle performance over a wide temperature range. x Mn y Co 1-x-y O 2 (x≥0.5) is considered to be a reliable positive electrode material for the next generation of lithium-ion batteries. Improving its charge cut-off voltage can directly increase the capacity by about 15–35%. However, this method will make the overall and surface of the positive electrode material more unstable, so it has higher requirements for the thermodynamic stability of the electrolyte. Traditional carbonate-based electrolytes are still irreplaceable for graphite negative electrodes, but their oxidation stability is poor at higher voltages (>4.3V), and the resulting series of interfacial side reactions cause the cycle life of the battery to drop sharply. In addition, the high melting point of cyclic carbonate solvents and their high solvation energy for lithium ions limit the application of lithium-ion batteries in lower temperature scenarios and high current charging and discharging processes. Therefore, designing an electrolyte with high oxidation stability and excellent interfacial compatibility over a wide temperature range is of great significance to promote the development of lithium-ion batteries. Summary of the invention
[0003] In order to solve the above problems, the present invention provides an electrolyte based on a linear sulfone solvent and its application and a lithium ion battery. The electrolyte has excellent oxidation stability and interface compatibility, and can achieve stable cycling of a 4.5V high-voltage lithium ion battery in a wide temperature range.
[0004] In order to solve the above technical problems, the present invention adopts the following technical solutions:
[0005] Provided is an electrolyte based on a linear sulfone solvent, comprising a linear sulfone solvent, a lithium salt, a co-solvent and an additive; wherein:
[0006] The linear sulfone solvent is one or more of dimethyl sulfone, methyl ethyl sulfone, diethyl sulfone, ethyl isopropyl sulfone, and dimethyl sulfoxide;
[0007] The co-solvent is one or more of 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether, 1,1,2,2-tetrafluoroethyl-2,2,2-trifluoroethyl ether, bis(2,2,2-trifluoroethyl) ether, 2,2,2-trifluoroethyl-1,1,2,3,3,3-hexafluoropropyl ether, difluoromethyl 2,2,3,3-tetrafluoropropyl ether, and fluoromethyl-1,1,1,3,3,3-hexafluoroisopropyl ether;
[0008] The volume ratio of the linear sulfone solvent to the co-solvent is 3:7 to 7:3.
[0009] According to the above scheme, the volume ratio of the linear sulfone solvent to the co-solvent is preferably 2:3-3:2. The linear sulfone solvent and the hydrofluoroether co-solvent are used in an appropriate ratio, which is more conducive to generating intermolecular hydrogen-like bond interactions based on the high dipole moment and exposed positive charge center of the linear sulfone solvent and the strong electronegativity of the fluorine atoms in the hydrofluoroether co-solvent, thereby reducing the coordination effect between the linear sulfone solvent and the lithium ion, weakening the solvation energy of the lithium ion, accelerating the desolvation process of the lithium ion, and improving the rate performance and low temperature performance of the lithium ion battery.
[0010] According to the above scheme, the lithium salt used is selected from lithium bis(trifluoromethylsulfonyl)imide (LiTFSI), lithium bis(fluorosulfonyl)imide (LiFSI), lithium hexafluorophosphate (LiPF 6 ), lithium tetrafluoroborate (LiBF 4 ) at least one of.
[0011] According to the above scheme, the molar concentration of the lithium salt in the electrolyte is 0.5 to 4 mol / L, preferably 0.5 to 1.5 mol / L.
[0012] According to the above scheme, the additive is lithium difluorooxalate borate. When the additive is lithium difluorooxalate borate, since it can simultaneously generate an interface film rich in lithium fluoride at the positive and negative electrodes, the cycle stability of the lithium-ion battery under high voltage can be further improved.
[0013] According to the above scheme, the mass fraction of the additive in the electrolyte is 0.01-5%, preferably 0.5%-2%.
[0014] Provided is an application of a sulfone solvent-based electrolyte in a lithium-ion battery.
[0015] Provided is a lithium-ion battery comprising a positive electrode material, a negative electrode material, a separator and the above electrolyte.
[0016] According to the above scheme, the positive electrode material is a nickel-cobalt-manganese ternary material or a lithium cobalt oxide material. Preferably, the nickel-cobalt-manganese ternary material is Li(Ni x Co y Mnz ) 2 ,x≥0.5,y>0,z>0,x+y+z=1.
[0017] According to the above solution, the negative electrode material is graphite.
[0018] According to the above solution, the diaphragm material is polypropylene (PP) or polyethylene (PE).
[0019] The beneficial effects of the present invention are as follows:
[0020] The invention provides an electrolyte based on a linear sulfone solvent, comprising a linear sulfone solvent, a lithium salt, a hydrofluoroether co-solvent and an additive, wherein the linear sulfone solvent has excellent oxidation resistance and safety, and has a high dipole moment and an exposed positive charge center, and the fluorine atom in the hydrofluoroether has a strong electronegativity, and a properly proportioned linear sulfone solvent and hydrofluoroether can generate a quasi-hydrogen bond interaction between molecules, so that the coordination effect between the linear sulfone solvent and the lithium ion is reduced, the solvation energy of the lithium ion is weakened, and the desolvation process of the lithium ion is accelerated. process, thereby improving the rate performance and low-temperature performance of lithium-ion batteries; at the same time, avoiding the continuous decomposition of solvent components on the surface of graphite negative electrode, thereby generating anion-dominated SEI film, improving the stability of graphite negative electrode; the electrolyte is used in lithium-ion batteries, and can be preferentially reduced on the surface of graphite negative electrode to form a stable interface film, so as to achieve 4.5V high-voltage batteries with high energy density, good cycle stability and large current charge and discharge capability in a wide temperature range (-20 to 60°C), excellent comprehensive performance, and important application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 The electrolyte obtained in Example 1 of the present invention is 1 H- 19 F HOESY spectrum.
[0022] Figure 2 The electrolyte obtained in Example 2 of the present invention is 1 H- 19 F HOESY spectrum.
[0023] Figure 3 The electrolyte obtained in Example 3 of the present invention is 1 H- 19 F HOESY spectrum.
[0024] Figure 4 The charge transfer impedance (R ct)The curves and charge transfer activation energy obtained by fitting the Arrhenius formula.
[0025] Figure 5 The charge transfer impedance (R ct )The curves and charge transfer activation energy obtained by fitting the Arrhenius formula.
[0026] Figure 6 The electrolyte prepared in Example 1, Comparative Example 3 and Comparative Example 4 described in Test Example 5 is LiNi 0.8 Co 0.1 Mn 0.1 O 2 The full battery was assembled with artificial graphite as the positive electrode and artificial graphite as the negative electrode. They were first activated for 2 weeks at a charge and discharge current of 0.1C / 0.1C, and then a performance comparison chart of the rate test was performed.
[0027] Figure 7 This is the surface electrostatic potential energy distribution diagram of methyl ethyl sulfone and cyclopentane sulfone.
[0028] Figure 8 For the electrolyte prepared in Example 1 described in Test Example 6, LiNi 0.8 Co 0.1 Mn 0.1 O 2 Performance diagram of a full battery assembled with artificial graphite as the positive electrode and the negative electrode, activated at 25°C at a charge and discharge current of 0.1C / 0.1C for 2 weeks, and then subjected to a long cycle test at -20°C.
[0029] Fig. 9 For the electrolyte prepared in Example 1 described in Test Example 6, LiNi 0.8 Co 0.1 Mn 0.1 O 2 Performance diagram of a full battery assembled with artificial graphite as the positive electrode and the negative electrode, activated at 25°C at a charge and discharge current of 0.1C / 0.1C for 2 weeks, and then subjected to a long cycle test at 60°C.
[0030] Fig.10 The electrolyte prepared in Example 1, Comparative Example 1 and Comparative Example 2 described in Test Example 7 is LiNi 0.8 Co 0.1 Mn 0.1 O 2The full battery was assembled with artificial graphite as the positive electrode and artificial graphite as the negative electrode. They were first activated at a charge and discharge current of 0.1C / 0.1C for 2 weeks, and then cycled at a charge and discharge current of 0.5C / 0.5C for 50 weeks. After the cycle, the SEI on the surface of the artificial graphite negative electrode was detected by X-ray photoelectron spectroscopy (XPS) to obtain the atomic ratio of sulfur element in different SEIs. DETAILED DESCRIPTION
[0031] In order to enable those skilled in the art to better understand the technical solution of the present invention, the present invention is further described in detail below with reference to the accompanying drawings.
[0032] Example 1
[0033] A configuration of an electrolyte based on a linear sulfone solvent is provided, comprising the following steps:
[0034] In a glove box filled with argon (water content <1 ppm, oxygen content <1 ppm), ethyl methyl sulfone (EMS) and 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether (TTE) were uniformly mixed in a volume ratio of 1:1, lithium bis(trifluoromethylsulfonyl)imide (LiTFSI) was added to the mixed solution until its molar concentration was 1.0 mol / L, and then lithium difluorooxalatoborate (LiDFOB) was added at a mass fraction of 1.0% of the electrolyte to obtain an electrolyte based on a linear sulfone solvent.
[0035] Example 2
[0036] The operation of this embodiment is the same as that of Embodiment 1, except that 1,1,2,2-tetrafluoroethyl-2,2,2-trifluoroethyl ether (TFTFE) is used instead of 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether (TTE) to obtain the electrolyte of this embodiment.
[0037] Example 3
[0038] The operation of this embodiment is the same as that of embodiment 1, except that bis(2,2,2-trifluoroethyl) ether (BTFE) is used instead of 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether (TTE) to obtain the electrolyte of this embodiment.
[0039] Example 4
[0040] The operation of this embodiment is the same as that of Embodiment 1, except that lithium bis(trifluoromethylsulfonyl)imide (LiFSI) is used instead of lithium bis(trifluoromethylsulfonyl)imide (LiTFSI) to obtain the electrolyte of this embodiment.
[0041] Example 5
[0042] The operation of this embodiment is the same as that of embodiment 1, except that lithium hexafluorophosphate (LiPF 6) is used instead of lithium bis(trifluoromethylsulfonyl)imide (LiTFSI) to obtain the electrolyte of this embodiment.
[0043] Example 6
[0044] The operation of this embodiment is the same as that of Embodiment 1, except that ethyl isopropyl sulfone (EiPS) is used instead of ethyl methyl sulfone (EMS) to obtain the electrolyte of this embodiment.
[0045] Comparative Example 1
[0046] In a glove box filled with argon (water content <1 ppm, oxygen content <1 ppm), lithium bis(trifluoromethylsulfonyl)imide (LiTFSI) was added to ethyl methyl sulfone (EMS) until the molar concentration reached 1.0 mol / L to obtain the electrolyte of this comparative example.
[0047] Comparative Example 2
[0048] The operation of this comparative example is the same as that of Example 1, except that no lithium difluorooxalatoborate (LiDFOB) additive is added to the electrolyte to obtain the electrolyte of this comparative example.
[0049] Comparative Example 3
[0050] In a glove box filled with argon (water content <1 ppm, oxygen content <1 ppm), ethylene carbonate (EC) and diethyl carbonate (DEC) were uniformly mixed at a volume ratio of 1:1, and lithium hexafluorophosphate (LiPF 6 ) until its molar concentration is 1.0 mol / L to obtain the electrolyte of this comparative example.
[0051] Comparative Example 4
[0052] The operation of this comparative example is the same as that of implementation 1, except that cyclopentane sulfone (SL) is used instead of ethyl methyl sulfone (EMS) to obtain the electrolyte of this comparative example.
[0053] Electrochemical testing and characterization
[0054] Test Example 1
[0055] The electrolytes of the above-mentioned embodiments and comparative examples were respectively made into CR2032 button batteries, wherein the button batteries comprise a positive electrode sheet, a negative electrode sheet, a separator, an electrolyte and battery auxiliary materials, wherein the positive electrode active material is a nickel-cobalt-manganese ternary material (LiNi 0.8 Co 0.1 Mn 0.1 O 2 ); the negative electrode active material is artificial graphite. LiNi 0.8 Co 0.1 Mn 0.1 O 2The positive electrode loading is 6 mg and the diameter is 12 mm. The diaphragm is Celgard-2400 with a diameter of 19 mm. The graphite negative electrode loading is 4 mg and the diameter is 12 mm. The amount of electrolyte used in each battery is 40 μL, and they are all first activated for 2 weeks at a charge and discharge current of 0.1C / 0.1C (1C=200mA / g) and a charge cut-off voltage of 4.5V to detect the first week coulomb efficiency of the battery. Subsequently, a long cycle test was carried out at a charge and discharge current of 0.5C / 0.5C and a charge cut-off voltage of 4.5V to detect the number of cycles of life, where the battery cycle life is calculated based on an 80% capacity retention rate.
[0056] The test results are shown in Table 1 below.
[0057] Table 1
[0058] Example / Comparative Example First week coulomb efficiency Cycle life Example 1 90.6% 667 Example 2 82.0% 327 Example 3 83.6% 305 Example 4 81.5% 310 Example 5 82.4% 366 Example 6 82.3% 400 Comparative Example 1 78.4% 150 Comparative Example 2 80.4% 102 Comparative Example 3 76.0% 47
[0059] Test Example 2
[0060] Interaction test between linear sulfone solvents and hydrofluoroether co-solvents: The electrolytes prepared in Example 1, Example 2, and Example 3 were used to test the interaction between linear sulfone solvents and hydrofluoroether co-solvents. 1 H- 19 F HOESY test. The results are as follows Figure 1-3 As shown in the figure, it can be seen that there is a spatial proximity between the hydrogen atoms in methyl ethyl sulfone and the fluorine atoms in the hydrofluoroether co-solvent, proving that there is a wide range of interactions between linear sulfone solvents and hydrofluoroether co-solvents.
[0061] Test Example 3
[0062] Charge transfer activation energy (E a ) Test: The electrolytes prepared in Example 1 and Comparative Example 1 were used to prepare LiNi 0.8 Co 0.1 Mn 0.1 O 2 The whole battery was assembled with graphite as the positive electrode and artificial graphite as the negative electrode. They were first activated for 2 weeks at a charge and discharge current of 0.1C / 0.1C, and the activated whole battery was subjected to a variable temperature impedance test in the temperature range of 0 to 60°C to obtain the relationship between the charge transfer impedance of different electrolytes and the temperature.
[0063] The results are as follows Figure 4-5 As shown in the figure, it can be seen that the introduction of hydrofluoroether co-solvents can significantly reduce the charge transfer activation energy of lithium-ion batteries when the type and concentration of lithium salts are consistent. This is because the interaction between methyl ethyl sulfone and hydrofluoroether co-solvents weakens the coordination between sulfone solvents and lithium ions, thereby reducing the solvation energy of lithium ions and accelerating the desolvation process of lithium ions, thereby improving the rate performance and low-temperature performance of lithium-ion batteries.
[0064] Test Example 4
[0065] Lithium ion migration number test: Li|Li symmetric batteries were assembled using the electrolytes prepared in Examples 1-3 and Comparative Examples 1-3, respectively, and the lithium ion migration numbers of various electrolytes were tested. The results are shown in the following table.
[0066] Table 2
[0067] Example / Comparative Example Lithium ion migration number Comparative Example 1 0.404 Comparative Example 2 0.526 Comparative Example 3 0.383 Example 1 0.640 Example 2 0.584 Example 3 0.559
[0068] From the results in Table 2, it can be seen that the introduction of hydrofluoroether co-solvents can significantly increase the lithium ion migration number of the electrolyte when the type and concentration of the lithium salt are consistent, and the lithium ion migration number of the electrolytes prepared in Examples 1-3 is significantly higher than that of commercial carbonate electrolytes. This is because the hydrogen-bond-like interaction between the linear sulfone solvent and the hydrofluoroether co-solvent promotes the transport of lithium ions in the electrolyte liquid phase, thereby increasing the migration number of lithium ions, thereby improving the high-current charge and discharge capacity of the lithium-ion battery.
[0069] Test Example 5
[0070] Rate performance test: The electrolytes prepared in Example 1, Comparative Example 3 and Comparative Example 4 were used to prepare LiNi 0.8 Co 0.1 Mn 0.1 O 2 The whole battery was assembled with graphite as the positive electrode and artificial graphite as the negative electrode. They were first activated for 2 weeks at a charge and discharge current of 0.1C / 0.1C, and the activated whole battery was tested for rate performance.
[0071] from Figure 6 The results show that the rate performance of the full battery decreased significantly when only methyl ethyl sulfone was replaced by cyclopentane sulfone. This is because the charge center of the cyclic sulfone molecules is dispersed on the ring, and its positive charge center is difficult to form a hydrogen bond-like interaction with the fluorine atom of the hydrofluoroether molecule ( Figure 7 ), and therefore cannot play the role of reducing the solvation energy of lithium ions like linear sulfone solvent molecules.
[0072] Test Example 6
[0073] High and low temperature performance test: The electrolyte prepared in Example 1 was used to 0.8 Co 0.1 Mn 0.1 O 2 The full battery was assembled with graphite as the positive electrode and artificial graphite as the negative electrode. They were first activated at a charge and discharge current of 0.1C / 0.1C for 2 weeks, and the activated full battery was subjected to long cycle tests at -20℃ and 60℃, respectively, with a charge cut-off voltage of 4.5V.
[0074] from Figure 8 and Fig. 9 The results show that the full battery using the electrolyte prepared in Example 1 can be stably cycled for more than 140 cycles at -20°C without capacity decay. It can be stably cycled for 200 cycles at 60°C with a capacity retention rate of 80.7%.
[0075] Test Example 7
[0076] Graphite negative electrode SEI film component test: The electrolytes prepared in Example 1, Comparative Example 1 and Comparative Example 2 were used to prepare LiNi 0.8 Co 0.1 Mn 0.1 O 2 The full battery was assembled with artificial graphite as the positive electrode and artificial graphite as the negative electrode. They were first activated at a charge and discharge current of 0.1C / 0.1C for 2 weeks, and then cycled at a charge and discharge current of 0.5C / 0.5C for 50 weeks. After the cycle, the SEI of the artificial graphite negative electrode was detected using XPS. The results are shown in Fig.10 shown.
[0077] From the results in the figure, it can be seen that regardless of whether the electrolyte contains lithium difluorooxalate borate additives, after adding hydrofluoroether co-solvents, the atomic ratio of sulfur in the SEI component decreases significantly. This is because after the solvation energy of lithium ions is reduced, sulfone solvents can be partially desolvated before decomposition, which significantly reduces the content of sulfone solvent decomposition components in the SEI component. Due to its high reduction potential, lithium difluorooxalate borate can be preferentially decomposed before sulfone solvents to generate inorganic-rich SEI, further reducing the content of sulfone solvent decomposition components in SEI, thereby improving the first-week coulomb efficiency and long-cycle performance of high-voltage lithium-ion batteries.
[0078] Obviously, the above embodiments are merely examples for clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from this are still within the protection scope of the invention.
Claims
1. An electrolyte based on a linear sulfone solvent, characterized in that: It includes linear sulfone solvents, lithium salts, co-solvents and additives; wherein: The linear sulfone solvent is one or more of dimethyl sulfone, methyl ethyl sulfone, diethyl sulfone, ethyl isopropyl sulfone and dimethyl sulfoxide; The co-solvent is one or more of 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether, 1,1,2,2-tetrafluoroethyl-2,2,2-trifluoroethyl ether, bis(2,2,2-trifluoroethyl) ether, 2,2,2-trifluoroethyl-1,1,2,3,3,3-hexafluoropropyl ether, difluoromethyl 2,2,3,3-tetrafluoropropyl ether, and fluoromethyl-1,1,1,3,3,3-hexafluoroisopropyl ether; The volume ratio of the linear sulfone solvent to the co-solvent is 3:7 to 7:
3.
2. The electrolyte according to claim 1, characterized in that The lithium salt used is selected from at least one of lithium bis(trifluoromethylsulfonyl)imide, lithium bis(fluorosulfonyl)imide, lithium hexafluorophosphate and lithium tetrafluoroborate.
3. The electrolyte according to claim 1, characterized in that The molar concentration of the lithium salt in the electrolyte is 0.5-4 mol / L.
4. The electrolyte according to claim 1, characterized in that The additive is lithium difluorooxalate borate.
5. The electrolyte according to claim 1, characterized in that The mass fraction of the additive in the electrolyte is 0.01-5%.
6. The electrolyte according to claim 1, characterized in that The volume ratio of the linear sulfone solvent to the co-solvent is 2:3 to 3:
2.
7. Use of the sulfone solvent-based electrolyte according to any one of claims 1 to 6 in a lithium-ion battery.
8. A lithium ion battery comprising a positive electrode material, a negative electrode material and a separator, characterized in that: Also includes the electrolyte according to any one of claims 1-6.
9. The lithium-ion battery according to claim 8, characterized in that: The positive electrode material is a nickel-cobalt-manganese ternary material or a lithium cobalt oxide material; the negative electrode material is graphite.
10. The lithium ion battery according to claim 8, characterized in that The diaphragm is made of polypropylene or polyethylene.
